A Chemometric Approach to Oxidative Stability and Physicochemical Quality of Raw Ground Chicken Meat Affected by Black Seed and Other Spice Extracts - Małgorzata Muzolf-Panek; Anna Kaczmarek; Jolanta Tomaszewska-Gras; Renata Cegielska-Radziejewska; Tomasz Szablewski; Małgorzata Majcher; Kinga Stuper-Szablewska (MDPI AG, 2020)
The effects of black seed (Nigella sativa), allspice, bay leaf, caraway, cardamom, clove, and nutmeg extracts on the quality of raw ground chicken legs stored at 4 °C were investigated. During 12 days of storage, conjugated diene (CD) content, thiobarbituric acid reactive substances (TBARS), oxidation induction time (IP) by DSC (differential scanning calorimetry), hexanal content by GC-SPME-MS, thiol group (SH) content were determined. Moreover, microbial growth, pH and color of the samples were investigated. Sensory analysis was also realized. All extracts increased oxidative stability and safety of meat, significantly changed the color of the samples, stabilized the pH and increased their sensory scores (except color of samples with bay leaf and black seed) when comparing to control. Black seed, allspice and clove extracts showed high antioxidant capacity in lipid (CD = 0.23%, 0.28%, and 0.37%, respectively; TBARS = 0.55, 0.50, and 0.48 mg/kg, respectively) and protein fraction (SH content = 47.9, 52.1 and 52.7 nmol/g, respectively), although the ABTS•+ radical scavenging activity of black seed (33.1 µM/g) was significantly lower than the cloves (2496 µM/g) and allspice (815 µM/g). In the sensory analysis the highest scores were ascribed to the sample with cardamom followed by cloves. Principal component analysis (PCA) indicated complex and inseparable interrelationship among lipid and protein oxidation processes and the relationship of the protein oxidation on the lightness of meat. The results enabled to discriminate the meat samples, showing a great impact of the extracts on the final quality of raw chicken meat with black seed being potent antioxidant active additive.